Not All Stressors Are Equal: Mechanism of Stressors on RPE Cell Degeneration - Tong, Yao; Wang, Shusheng (Frontiers in Cell and Developmental Biology, 2020)
Age-related macular degeneration (AMD) is a major cause of irreversible blindness among the elderly population. Dysfunction and degeneration of the retinal pigment epithelial (RPE) layer in the retina underscore the pathogenesis of both dry and wet AMD. Advanced age, cigarette smoke and genetic factors have been found to be the prominent risk factors for AMD, which point to an important role for oxidative stress and aging in AMD pathogenesis. However, the mechanisms whereby oxidative stress and aging lead to RPE cell degeneration are still unclear. As cell senescence and cell death are the major outcomes from oxidative stress and aging, here we review the mechanisms of RPE cell senescence and different kinds of cell death, including apoptosis, necroptosis, pyroptosis, ferroptosis, with an aim to clarify how RPE cell degeneration could occur in response to AMD-related stresses, including H2O2, 4-Hydroxynonenal (4-HNE), N-retinylidene-N-retinyl- ethanolamine (A2E), Alu RNA and amyloid beta. Besides those, sodium iodate (NaIO3) induced RPE cell degeneration is also discussed in this review. Although NaIO3 itself is not related to AMD, this line of study would help understand the mechanism of RPE degeneration.